Extraction of terms for the construction of semantic frames for named bays - Rojas-García, Juan; Faber, Pamela (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
EcoLexicon (http://ecolexicon.ugr.es) is a terminological knowledge base on environmental science, whose design permits the geographic contextualization of data. For the geographic contextualization of LANDFORM concepts, this paper presents a semi-automatic method of extracting terms associated with named bays (i.e., Greenwich Bay). Terms were extracted from a specialized corpus, where named bays were automatically identified. Statistical procedures were applied for selecting both terms and bays in distributional semantic models to construct the conceptual structures underlying the usage of named bays. The bays sharing associated terms were also clustered and represented in the same conceptual network. The results showed that the method successfully described the semantic frames of named bays with explanatory adequacy, according to the premises of Frame-based Terminology.